Arterial thrombosis in homozygous antithrombin deficiency - Olivieri, M.; Bidlingmaier, C.; Schetzeck, S.; Borggräfe, I.; Geisen, C.; Kurnik, K. (Hämostaseologie, 2012)
Antithrombin (AT), a serin protease inhibitor (serpin) produced in the liver, inhibits mainly thrombin and factor Xa. Antithrombin deficiency (AD) is associated with a higher incidence of thrombosis. Case report: We report a newborn with uncomplicated birth in the 40+5 week of gestation and postnatal appearance of a reticular, livide haematoma on the right upper arm and a tonic clonic epileptic seizure. Clinical examination revealed weak pulses in the A. radialis and ulnaris. MRI scan showed a large thrombus in the A. carotis interna and externa with large cerebral infarction and a thrombus in the A. subclavia. Laboratory work up showed elevated D-dimers and antithrombin levels < 20% (lowest 15%), age-related values for protein C, protein S, plasminogen, and no other inherited thrombophilia. Therapy: We started anticoagulation with unfractionated heparin intravenously (aPTT: 50–60 s) and under suspicion of an AD the substitution of AT (70 U/kg body weight). In course of time we changed anticoagulation to low molecular weight heparin (Anti Xa 0.6–0.8 U/ml) and substitution of 250 E/kg AT every second day. In the molecular work up we found a homozygous missense mutation in exon 2 of SERPINC1 gene (type „Budapest 3”). Molecular analysis showed also heterozygous mutations in both parents and a homozygous mutation in the asymptomatic brother aged three years. At age of six months we changed the anticoagulation to coumadin (INR 2.5–3.5). Anticoagulation with coumadin was also started in the brother. Discussion: Hereditary AD is associated with an increased risk of thrombosis. The homozygous status mainly leads to intrauterine fetal loss or the occurrence of peri- and postnatal thrombosis. Therapy consists in the substitution of AT and a lifelong anticoagulation with vitamin K antagonists also in asymptomatic patients.
Keywords: Arterial thrombosis; antithrombin deficiency; inherited thrombophilia; anticoagulation